Dimensions of blackness : racial identity and political beliefs - Sullivan, Jas M.; Winburn, Jonathan, 1977-; Cross, William E., 1940- (State University of New York Press, 2018)
While the dynamics of racial oppression limit the range of attitudes blacks may construct and hold, their basic humanity introduces additional attitudinal variance that is nearly boundless. Rather than claim it is possible to conceptualize and measure every iteration of blackness, modern social theorists such as Robert Sellers and William Cross Jr. contend that one should systematically "sample" the unmanageable range of different identity frames found among blacks. In Dimensions of Blackness, the authors suggest there is no single, solitary way to express black racial identity. They move away from blackness as binary and instead reveal what happens when black racial identity is conceptualized with "difference of opinion." Using a multidimensional perspective this book explores whether black racial identity differences among blacks influence political attitudes and behavior--Back cover
Keywords: African Americans -- Race identity.; African Americans -- Politics and government.; African Americans -- Social conditions.; United States -- Race relations.; United States -- Politics and government.; United States -- Social conditions.; Noirs américains -- Identité ethnique.; Noirs américains -- Politique et gouvernement.; Noirs américains -- Conditions sociales.; États-Unis -- Relations raciales.; États-Unis -- Politique et gouvernement.; États-Unis -- Conditions sociales.; POLITICAL SCIENCE -- Political Freedom & Security -- Civil Rights.; POLITICAL SCIENCE -- Political Freedom & Security -- Human Rights.; African Americans -- Politics and government; African Americans -- Race identity; African Americans -- Social conditions; Politics and government; Race relations; Social conditions; United States